ANALISIS FAKTOR KOMUNIKASI, KONSEP DIRI, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN METODE MIX METHOD PADA KARYAWAN BANK SYARIAH INDONESIA KCP TULUNGAGUNG SUDIRMAN - Familda Anggun Parastika; Mega Tunjung Hapsari (Reinforce: Journal of Sharia Management, 2022)
This research is motivated by the importance of employee performance because employees are the driving force for the company's success. Aims to test and analyze the effect of communication, self-concept, and work environment on job satisfaction of employees of Bank Syariah Indonesia KCP Tulungagung Sudirman. The method used is a mix method with the type of research that combines quantitative and qualitative analysis (Sequantial Explanatory). The sample in this study were 27 employees of BSI KCP Tulungagung. Quantitative data multiple linear analysis test and hypothesis test. Qualitative data analysis using triangulation. Based on the research, partial results were obtained and communication stimulants, self-concept, and work environment had a positive effect on job satisfaction of employees of Bank Syariah Indonesia KCP Tulungagung Sudirman. To strengthen quantitative research, qualitative analysis was carried out by interviewing 6 informants whose results supported the results of quantitative data. Practical implications apart from developing research with mixed methods in human resource management, the research results can be used as recommendation materials to assess employee performance.